2015
DOI: 10.1080/02701367.2015.1049691
|View full text |Cite
|
Sign up to set email alerts
|

How Coaches’ Motivations Mediate Between Basic Psychological Needs and Well-Being/Ill-Being

Abstract: Our results highlight that 3 conditions seem necessary for coaches to experience psychological well-being in their teams: basic psychological needs satisfaction, especially relatedness; lack of basic psychological needs thwarting; and self-determined motivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 27 publications
2
48
0
1
Order By: Relevance
“…33, nº 1 (january) situations where they felt integrated, valued and well-related fostered their need for relatedness, and were clearly related to their well-being. Although Deci and Ryan's study (2000) highlighted that the needs for autonomy and competence are essential to experience autonomous motivation and well-being, recent studies have shown the relevant role of the BPN for relatedness (Alcaraz et al, 2015;McLean & Mallett, 2012). In a study conducted with development coaches, Alcaraz et al, (2015) found that among the three needs, relatedness was the one that mostly predicted coaches' self-determined motivation and psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33, nº 1 (january) situations where they felt integrated, valued and well-related fostered their need for relatedness, and were clearly related to their well-being. Although Deci and Ryan's study (2000) highlighted that the needs for autonomy and competence are essential to experience autonomous motivation and well-being, recent studies have shown the relevant role of the BPN for relatedness (Alcaraz et al, 2015;McLean & Mallett, 2012). In a study conducted with development coaches, Alcaraz et al, (2015) found that among the three needs, relatedness was the one that mostly predicted coaches' self-determined motivation and psychological well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Although Deci and Ryan's study (2000) highlighted that the needs for autonomy and competence are essential to experience autonomous motivation and well-being, recent studies have shown the relevant role of the BPN for relatedness (Alcaraz et al, 2015;McLean & Mallett, 2012). In a study conducted with development coaches, Alcaraz et al, (2015) found that among the three needs, relatedness was the one that mostly predicted coaches' self-determined motivation and psychological well-being. In a similar way, McLean & Mallett (2012) found in their qualitative study that BPN for relatedness was also very important for coaches of different competitive levels (i.e., participation, development and highperformance).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Stebbings, Taylor, and Spray (2015) argued that coaches who experience higher levels of positive affect are more likely to trust their athlete's abilities and encourage empowering possibilities for these athletes. This is supported by Alcaraz, Torregrosa, and Viladrich (2015), who suggested that coaches who experience psychological well-being more likely develop healthy relationships with athletes.…”
Section: This Difficulty As Followsmentioning
confidence: 72%
“…However, we believe that our study draws interesting interpretations on how social agents in sport might influence the emotional experience of young sport participants besides modeling their type of motivation. Further studies should complement these environmental antecedents with other dispositional variables related to the cognitive appraisal of the competition (Martinent and Ferrand, 2015), including for instance perfectionism (Appleton and Hill, 2012), or coping strategies (Dias et al, 2012), as well as to depict the antecedents of coaches’ motivation to develop one specific interpersonal style (Stebbings et al, 2011; Alcaraz et al, 2015a,b). …”
Section: Discussionmentioning
confidence: 99%